Pendampingan K3 Berbasis Identifikasi Bahaya dan Penataan Lingkungan Kerja pada Industri Rumah Tangga Bata Ringan - Puspa Ningrum; Yuharika Pratiwi; Husnah Husnah; Toni Hartono Bagio (Fakultas Teknik Universitas Cenderawasih, 2026)
This community service program addressed occupational safety and health (OSH) problems in a home-based lightweight brick industry in Pekanbaru, including cement and sand dust, manual material handling, obstructed work pathways, disorganized material storage, and inconsistent use of personal protective equipment (PPE). The program aimed to improve OSH knowledge, PPE compliance, and workplace conditions through integrated education and participatory workplace assistance. A descriptive pre-post approach was applied to 25 participants, with 10 active workers serving as the primary targets for behavioral and workplace observations. Activities comprised initial situation analysis, OSH education, PPE demonstrations, participatory hazard identification, workplace arrangement, installation of safety posters, and evaluation using pre-test/post-test instruments, observation sheets, and workplace checklists. The indicator scores increased from 42% to 82% for OSH knowledge, from 48% to 85% for PPE compliance, and from 50% to 87% for workplace conditions. The program also produced designated storage areas, clearer worker pathways, and on-site OSH educational media. These findings indicate immediate improvements after the intervention; however, sustained implementation requires simple work procedures, designated responsibility, and periodic monitoring.